Risk factors of acute kidney injury in pediatric acute lymphoblastic leukemia with hyperleukocytosis - Kinanti, Rengganis Ayu; Palupi-Baroto, Retno; Sutaryo, Sutaryo (Paediatrica Indonesiana, 2023)
Background Acute kidney injury (AKI) can be found in pediatric acute lymphoblastic leukemia (ALL) patients with hyperleukocytosis. Acute kidney Injury (AKI) increases hospital length of stay and mortality. Previous studies have only reported the AKI incidence in ALL patients with hyperleukocytosis, without clarifying risk factors attributed to AKI incidence. Objective To determine the risk factors of AKI in pediatric ALL patients with hyperleukocytosis. Methods A case-control study was conducted in children aged 1-18 years admitted to Dr. Sardjito Hospital (RSUP Dr. Sardjito), Yogyakarta, Central Java Total population sampling of pediatric ALL patients with hyperleukocytosis and AKI was used for the case group, and a simple random sampling ratio of 1:2 was used for the control group. Cut-off values for each independent variable were determined by receiver-operator characteristic (ROC) curves. Bivariate and multivariate analyses were performed on potential risk factors. Results Fourteen pediatric ALL patients with hyperleukocytosis and AKI were included in the case group and 28 children with ALL and hyperleukocytosis but without AKI were included in the control group. The incidence of AKI in children with ALL and hyperleukocytosis was 15.4%. Multivariate analysis revealed that the significant risk factors of AKI in ALL patients with hyperleukocytosis were phosphate concentration ?5.15 mg/L (OR 10.43; 95%CI 1.38 to 79.04; P=0.02) and uric acid concentration ?9.08 mg/dL (OR 12.39; 95%CI 1.88 to 81.44; P=0.009). Conclusion Phosphate concentration ?5.15 mg/L and uric acid ?9.08 mg/dL were risk factors of AKI in pediatric ALL patients with hyperleukocytosis.